Evaluating attitudes to safety leadership within rail construction projects - Stiles, Shelley; Ryan, Brendan; Golightly, David (Elsevier, 2018)
Safety leadership is widely discussed, commonly relating to improving safety performance within an occupational environment. Whilst there is considerable research on the characteristics of positive and negative safety leadership behaviours, research to date does not evaluate these in the context of rail construction projects, with no specific consideration of the complex interfaces and challenges faced by temporary configurations of Client, Principal Contractor and Supply Chains within this sector. Twenty-one in-depth interviews were undertaken with representatives from Client, Principal Contractor and Supply Chain, to identify attitudes to safety leadership and consider how this may impact on safety performance. The level of understanding of safety leadership as a topic was evaluated against how well the study participants could explain the concept, and whether they could provide any examples of real world application. A total of 26 different examples of safety leadership interventions from the rail construction sector were identified from this study. These mostly aligned to nine good safety leadership areas identified within the literature, such as increasing visibility around safety, workforce involvement, providing recognition for good safety performance and ensuring effective communications. Half of the intervention examples provided were based around communications, in particular opportunities for leader engagement or the sharing of information. This study has identified that there are numerous safety leadership interventions being deployed within the rail construction sector, with the likely success of these leadership interventions being influenced by five themes; context, preparation, communication, leadership behaviour and style, and action.